Relationship Between Segregation and School Climate in Chilean Schools with High Scores Pisa 2009 [Relación Entre Segregación y Convivencia Escolar en Escuela Públicas Chilenas] - Bilbao-Ramirez, M (Pontificia Universidad Javeriana, 2016)
Chilean education is highly segregated, making it difficult to construct cohesive and democratic societies. Through a mixed-method sequential design we explored the relationship between segregation (selection and socioeconomic level) and quality of school climate, taking as example the 200 Chilean schools who participated in the PISA 2009 test. The results evidence worst school environments in public, non-selective and low socioeconomic status schools, where students feel stigmatized and discriminated by academic, social, family and political variables. We discuss the need to revise the education policy that encourages competition among schools for academic performance and training in civics to move towards more integrated schools and more democratic societies.